Juridical Analysis In Implementing Criminal Sanctions Against Gambling In Tangerang District - Mofea, Sukhebi; Komariah, Mamay; Saptudin, Fajar (The International Journal of Law Review and State Administration, 2023)
This study aims to discover the legal consequences of gambling crime and the Judge's considerations in deciding case number (2364/PID.B/2020/PN.TNG) regarding the corruption of gambling, which causes anxiety for the community. This research method uses a normative description approach according to the concept, legal basis, and legislation. Observation data collection techniques to research locations by observing actual events. Interviews with related parties, prosecutors, judges, lawyers, and defendants. Documentation studies include archives, electronic media containing gambling-related news, and archives. The research results conclude that the Defendant has been legally and convincingly proven guilty of committing the crime of gambling. That Defendant, in carrying out the Pakong and Togel type of gambling, did not have a special way to win the gambling game because it was only chance, and the Defendant placed the Pakong and Togel gambling without permission from the authorities.